The Influence of Financial Planning on Investment Decision Making: Qualitative Analysis - Dasinapa, Margaretha Beatrik (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to analyze the effect of financial planning on investment decision-making, focusing on how good planning can help investors make more rational decisions about dealing with market fluctuations and reduce the influence of psychological bias. Research Design and Methodology: This study uses a qualitative approach with in-depth analysis through structured interviews. The collected data is analyzed to identify how investors formulate their financial plans and how psychological factors influence investment decisions. Findings and Discussion: The results show that sound financial planning helps investors manage risk and stay focused on long-term goals despite market volatility. The study also found that investors with structured financial plans are better able to avoid impulsive decisions and reduce the influence of psychological biases such as anchoring bias and confirmation bias. In addition, portfolio diversification has proven to be an effective strategy in maintaining portfolio stability. Implications: This research provides a practical contribution for financial managers and investors by emphasizing the importance of comprehensive financial planning and diversification strategies in maintaining long-term financial stability. These findings can be a reference for developing more effective investment policies and supporting better financial literacy among investors.